Case grammar and its implications to developing writing skills - MOUMENE, Ahmed (Journal of Human Sciences, 1999)
This article exposes the existing controversy among researchers about the role of traditional grammar in helping students to overcome their grammatical errors. It consequently shows the relevance of Fillmore’s Case Grammar to developing writing skills and improving linguistic proficiency. The strength of this semantic grammar lies in its "universalism and "generativism". It enables its users to generate an infinitude of sentences and to avoid the burden of negative transfer. It also offers new strategies to understand, analyse and criticise the novel and the short story in an objectively-satisfying manner.